Sclerostin-dependent mechanisms of osteoporosis in patients with type 2 diabetes and obesity - Marchenko , Anastasia (The Ukrainian Scientific Medical Youth Journal, 2023)
during the examination of 103 patients with type 2 diabetes (DM), which in 83 cases took place against the background of increased body weight or obesity, has shown an abnormal increase in the content of sclerostin in blood serum, which had a direct correlation with body mass index. It has been suggested that changes in the levels of this glycoprotein, which is a member of the group of antagonist of bone morphogenetic protein, occur as a result of many processes in the body: an increase in the synthesis of TNF-α by adipocytes, vascular endothelium, neuroglial cells against the background of pre- and menopause, which contributes to bone tissue disoders i.e. osteoporosis. Endocrine osteoporosis is the largest group of secondary osteoporosis, the leading cause of which is type 2 diabetes mellitus. In the case of type 2 diabetes mellitus occuring against the background of obesity, prerequisites for the development of osteoporotic conditions are formed, one of the mechanisms for the development of which may be the glycoprotein sclerostin. The purpose of the study was determination of the structural and functional state of bone tissue by the sclerostin levels examination in patients with type 2 diabetes mellitus, which occurs against the background of topographic features of the distribution of adipose tissue. 103 patients with DM2 were involved in the work, which in 83 cases was combined with overweight or obesity (the main group). The comparison group included 20 patients with DM2, which an unchanged body mass index (BMI). The age of the patients ranged from 31 to 55; average age in groups was 43±4.6 years and 44.1±2.1 years, respectively. In both groups of patients men predominated 44 (53%) and 11 (55%) respectively. The duration of the disease was recorded in the range from 1 to 13 years. Determination of the distribution of adipose tissue in the body was studied using scales for characterizing body composition - OMRON BF511 (Japan). The content of visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) was identified. The activity of sclerostin in blood serum was determined by the immunoenzymatic method using commercial test systems "Biomedica" (USA) according to the instructions on the immunoenzymatic analyzer "Labline-90" (Austria). Processing of the obtained data was carried out by the method of variational statistics with the help of licensed software Stata 10 ("StatSoft Inc.", USA). Testing for normality of data distribution was performed using the Shapiro-Wilk test. For parameters with a normal distribution, the mean (M) ± standard error of the mean (m) was calculated. The obtained results were considered statistically significant at p<0.05. An increase in BMI was accompanied by a growth in the sclerostin index. That is the detected changes in the glycoprotein, which is included in the group of antagonists of bone morphogenetic proteins, suggest a violation of the osteoblast differentiation process. Those as DM2 so as a quantitative change in adipose tissue with its redistribution negatively affect the metabolism of bone tissue. The course of diabetes mellitus is accompanied by an increase in the activity of pro-inflammatory cytokines, namely, TNF-α, a component of the cytokine cascade of adipose tissue. This phenomenon is also associated with involvement of blood vessels in the process (endothelial cells produce this cytokine), nervous tissue (involvement of neuroglia cells) and metabolic shifts in the body. In addition, F.Xu et al. the experiment proved that osteoclastogenesis is inhibited in hyperglycemic and hyperinsulinemic states. That is, in patients with diabetes, with an increase in BMI, a negative "tandem" is formed due to the additional supply of TNF-α from many cells and an increase in the synthesis of sclerostin, which not only "starts" the process of bone mineral density disturbance, but also maintains it throughout the course of the disease. Also, a certain role is given to the age aspect of the examined patients with DM2, which also contributes to the inhibition of bone metabolism. In this case, an increase in the activity of sclerostin in combination with a negative background (obesity, menopause) can be considered as one of the mechanisms of the formation of osteoporotic changes. At the same time, the mechanisms of primary and secondary osteoporosis are combined, which strengthens and accelerates the process of bone architecture disruption. In patients with type 2 diabetes mellitus in combination with obesity conditions for a decrease in the quality of bone tissue due to a slowdown in bone metabolism occur, which contributes to the formation of osteoporotic conditions.